A Simple Microfluidic Device for Generating Solute Concentration Gradients. (2019) - Has, Chandra; Dhuriya, Rakhi; Sunthar, P.
Abstract: The major focus of the present study is to develop a simple microfluidic device to generate a stable concentration gradient of solute in a flow-free regime. The microfluidic device is prepared using photolithography and soft lithography techniques. The device consists of two reservoirs for two different fluids in which one of the fluids contains the solute component. The reservoirs are connected through the main channel in which solute concentration gradient is generated by diffusion of solute molecules. Further, the mid position of this main channel is connected to a vertical channel. Here, we show a generation of linear solute gradient sustainable up to 2 h. This novel technique of generating solute gradient can be used in future to study phoretic motion, chemotaxis or any other phenomenon where maintaining steady gradient plays an important role